2018
DOI: 10.1055/s-0038-1645889
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Multimedia Medication Reconciliation Software: A Randomized Controlled, Single-Blind Trial to Measure Diagnostic Accuracy for Discrepancy Detection

Abstract: ClinicalTrials.gov Identifier: NCT02135731.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 104 publications
(187 reference statements)
1
9
0
Order By: Relevance
“…8 13 14 In previous facility-level QI pilots within the VA, our team identified an array of sociotechnical issues mediating successful adoption. [15][16][17][18][19][20][21] These findings echo prior research on MR implementation barriers including limited EHR interoperability (including prescription data), poor interface usability, competing organisational priorities, patient-centred social factors (eg, health literacy), and clinician time and staff resource constraints. 5 22-28…”
Section: What This Study Addssupporting
confidence: 58%
See 1 more Smart Citation
“…8 13 14 In previous facility-level QI pilots within the VA, our team identified an array of sociotechnical issues mediating successful adoption. [15][16][17][18][19][20][21] These findings echo prior research on MR implementation barriers including limited EHR interoperability (including prescription data), poor interface usability, competing organisational priorities, patient-centred social factors (eg, health literacy), and clinician time and staff resource constraints. 5 22-28…”
Section: What This Study Addssupporting
confidence: 58%
“…Typically, sustained improvement in MR processes and clinical outcomes is contingent on a combination of decision support technologies, a strong organisational climate and a schematised workflow. 16 19 24 28 Unfortunately, our findings indicate that VA clinicians struggle with resource and technology gaps. They cited concerns over workflow compatibility and institutional support-including resources, time and leadership prioritisation.…”
Section: Principal Findingsmentioning
confidence: 89%
“…Interestingly, results of multicomponent interventions within the primary care setting were more equivocal, with only 7 of the 10 studies reporting positive findings. Furthermore, all of the studies reporting null effects in the primary care setting were randomized controlled trials, 44 , 72 , 85 possibly indicating that bias associated with nonrandomized and observational study designs may be inflating the observed effect estimates in secondary care settings. 94 Inflated positive results, where randomization and blinding are not possible, also raise the possibility of the Hawthorne effect where subjects modify their behavior in response to being observed or measured.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to MT, this information is imported into the EHR and reviewed by clinicians [ 31 ]. In their evaluation, they found similar rates of discrepancies (29%-39% vs 34%-40%), and the overall number of patients with discrepancies were similar (91%-99% vs 92%-93%) [ 33 , 34 ]. When evaluating the implementation of their application, they also found that time is a factor in using medication reconciliation technology and that, to be taken up, the technology needs to be well integrated into current workflows [ 35 ].…”
Section: Discussionmentioning
confidence: 99%